Pengaruh Gaya Belajar terhadap Pemahaman Kognitif Materi Hidangan dari Telur di SMK Negeri 2 Kota Mojokerto - Elyza Monic Novanda; Nugrahani Astuti; Andika Kuncoro Widagdo; Asrul Bahar (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
Learning activities that were well-prepared can stimulate people have well-prepared in the learning process. Three kinds of learning styles are visual, auditory, and kinesthetic. The learning style guides the teacher to appropriate methods to conduct the lessons. Based on the statement, the research aims to determine the influence of learning style and implemented in cognitive comprehension in egg dish. The subject to conduct this research were grade XI Culinary students at SMKN 2 Kota Mojokerto. The research design used ex post facto using the one-way ANOVA test. The researcher used questionnaire techniques, test methods, and documentation for collecting the data. The results showed that (1) the dominant learning style in the auditory learning style was 40.4% (19 students), while the visual learning style was 38.3% (18 students), and the kinesthetic learning style was 21.3% (10 students). (2) The average post-test score is 78.2. In the value range 71 – 85 with 21 out of 47 students. Based on the data analysis, the researcher found that learning style does not affect cognitive comprehension. It is shown in the sign one-way ANOVA value of 0.394 > 0.05, while the Fcount test is 0.952 <3.20 Ftable, so H0 is accepted and Ha is rejected.